Coordination Switch Drives Selective C−S Bond Formation by the Non‐Heme Sulfoxide Synthases. (15th November 2022) - Wu, Peng; Gu, Yang; Liao, Langxing; Wu, Yanfei; Jin, Jiaoyu; Wang, Zhanfeng; Zhou, Jiahai; Shaik, Sason; Wang, Binju
Abstract: The non‐heme iron ergothioneine synthase (EgtB) is a sulfoxide synthase that catalyzes oxidative C−S bond formation in the synthesis of ergothioneine, which plays roles against oxidative stress in cells. Despite extensive experimental and computational studies of the catalytic mechanisms of EgtB, the root causes for the selective C−S bond formation remain elusive. Using quantum mechanics/molecular mechanics (QM/MM) calculations, we show herein that a coordination switch of the sulfoxide intermediate is involved in the catalysis of the non‐heme iron EgtB. This coordination switch from the S to the O atom is driven by the S/π electrostatic interactions, which efficiently promotes the observed stereoselective C−S bond formation while bypassing cysteine dioxygenation. The present mechanism is in agreement with all available experimental data, including regioselectivity, stereoselectivity and KIE results. This match underscores the critical role of coordination switching in the catalysis of non‐heme enzymes. Abstract : Calculations suggest that a coordination switch of the sulfoxide intermediate is involved in the catalysis of ergothioneine synthase (EgtB). This coordination switch from S to O is driven by the S/π nonbonding electrostatic interactions, which efficiently promotes the observed stereoselective C−S bond formation while bypassing cysteine dioxygenation.